The Evaluation of Error Types and Turnaround Time of Preanalytical Phase in Biochemistry and Hematology Laboratories - Gokhan Cakirca (Iranian Society of Pathology, 2018)
Background& Objective: Each laboratory should determine the type of errors and turnaround time (TAT), especially in the preanalytical phase to report quality and timeliness of the test results. The current study aimed at investigating the common causes of preanalytical errors in biochemistry and hematology laboratories and evaluating the preanalytical TAT for outpatient samples. Methods: Data of rejected samples in the laboratory information system from September 2014 to September 2015 were retrospectively reviewed. Also, the preanalytical TAT of the outpatient samples was evaluated over the period of three months from June to August 2015. Preanalytical TAT was calculated from order entry to barcode scanning in the autoanalyzer. Results: With respect to the ratios of blood sample transfers, 1% of samples (2305 out of 225,563) in the hematology laboratory and 0.6% (1467 out of 255,943) in the biochemistry laboratory were rejected. The most common cause of rejection in the hematology and biochemistry laboratories was insufficient volume (48.8%) and hemolyzed sample (74.1%), respectively. The average preanalytical TAT for the outpatient samples was 62.3 minutes.The preanalytical TAT accounted for 10.8% (order entry-sample collection), 49% (sample collection-sample receipt), and 40.2% (sample receipt-barcode scanning in the autoanalyzer), respectively. Conclusion: Of all the samples received in the biochemistry and hematology laboratories, the overall percentage of rejections were 0.6% and 1%, respectively. The main target to improve preanalytical TAT was determined as the transportation (sample collection-sample receipt) step.